The journey begins: a narrative inquiry into the mentorship and support of novice principals - Waido, Anna Colleen, author; Lucero, Rodrick, advisor; Cooner, Donna, committee member; McKelfresh, David, committee member; von Fischer, Joe, committee member (Colorado State University. Libraries, 2013)
The purpose of this narrative inquiry was to understand the novice principals' experiences in the principalship and the support they received from their district to make recommendations for principal mentorship programs. The study reported on qualitative interview methods with three novice principals and two mentors to determine essential elements for mentorship programs and leadership development. The retelling of the stories validated the personal experiences the researcher had as a novice principal. The collective responses from the leaders provided new possibilities for the mentorship and support of novice principals. The study investigated the relationships between the mentor/mentee, the structures of different mentorship programs, and the components that were delivered for training new principals. The key findings from the analysis constructed what novice principals and mentors determined were effective methods to better support school leaders. The following themes emerged to support novice principals: 1. Mentor with meaning and purpose 2. Prepare novice principals for the realities of the position 3. Leadership skills and professional growth 4. Students are the priority The mutual benefits and support for the mentors and novice principals were used to design a Principal Mentorship Program. The program proposal is meant to have an effective leader in every school, create professional development and learning for principals, and align expectations for administrators across the district. The Principal Mentorship Program is designed for school districts to provide a systematic approach and structure to support new principals and mentors.
Keywords: leadership development; mentor; mentorship; novice principal; principal; support